PERANAN KEMENTRIAN AGAMA DALAM PENDIDIKAN ISLAM DI INDONESIA - Imam Sanusi; Bahaking Rama; Muhammad Rusdi Rasyid (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The Ministry of Religion is one of the government agencies, especially in the field of Islamic Education. This is certainly able to make this an advantage and convenience in creating the development of Islamic education in its work area which is superior to other work areas. The research method used in this research is a qualitative descriptive study. Data collection techniques through observation, interviews, and documentation studies. The results of this study indicate that in general education policies in the aspect of developing/developing Islamic Education at the Ministry of Religion of West Kalimantan are more mandated than the Ministry of Religion of the Republic of Indonesia. However, in practice these programs are relatively easier to implement, one of which is even though the coverage area is very wide. Institutionally, the ministry of religion in the framework of the development policy of fostering Islamic education in the Ministry of Religion West Kalimantan divides management responsibility into three work units, namely the Islamic Religious Education Section (PAPKIS), Madrasah Education Section (PENMAD) and Early Education and Islamic Boarding Schools Section (PD PONTREN). The Islamic Education Section (PAIS) has a working area for fostering and managing Islamic education in public schools at all levels, the Madrasah Education Section (PENMAD) for Islamic education oversees all levels in Madrasas and the Early Education and Islamic Boarding Schools Section (PD PONTREN) is responsible for responsible for fostering the ongoing Islamic education in Madrasas. The Role of the West Kalimantan Office of the Ministry of Religion in Islamic Education Development Policy Diniyah includes TPA and Islamic Boarding Schools, so that each section has a policy for developing Islamic Education in its own work program.